Painel I: - Atos de concentração globais – jurisdição soberania global - Grinberg, Mauro; Mattos, Ubiratan; Ramos, Rui de Moura; Powell, Mark; Farina, Elizabeth; Marques, Fernando (Revista do IBRAC, 2025)
SOBERANIA GLOBAL ................. 5 Coordenador/Chairman: Dr. Mauro Grinberg ................. 5 Dr. Ubiratan Mattos ................. 5 Dr. Mauro Grinberg ................. 6 Prof. Rui de Moura Ramos ................. 7 Dr. Mark Powell ................. 15 Profa. Elizabeth Farina ................. 59 Prof. Fernando Marques ................. 61 DEBATES ................. 63 PAINEL II ................. 78